Urgensi Prestasi Belajar Bidang Studi Fiqih dalam Meningkatkan Amal Ibadah Siswa - Rahmanto, Sarwo Edi; Muthoharoh, Miftakhul (LPPM STAI Ihyaul Ulum Gresik, 2022)
Student achievement is needed to improve student charity. The habit of doing good deeds should be caused by the acquisition of competent learning in students, especially from fiqh subjects. From this background, there are several main questions, 1) How is the urgency of student achievement in the field of jurisprudence in improving student charity at MAN 1 Mojokerto? 2) What are the obstacles faced in relation to student achievement in the field of fiqh studies in improving student charity at MAN 1 Mojokerto? This type of research uses qualitative methods with a descriptive pattern field research approach. This study also uses the theoretical framework of student achievement and student worship. This study came to the findings that 1) The urgency of student achievement in the field of fiqh studies in improving student charity at MAN 1 Mojokerto must include the involvement of parents. Students who are gifted in religious arts must be accompanied by teachers who will be more focused in growing obedience and constancy in their religious practice activities. 2). There are two obstacles faced in relation to student achievement in the field of fiqh studies in improving student worship at MAN 1 Mojokerto, namely internal constraints that rely on the psychological personality of students and external constraints in the form of the residential environment and social environment. Both require parental intervention and the seriousness of the PAI and BK teachers in guarding and monitoring the development of students' interests so that it leads to good habits of student worship.